Unregistered Marriage in the Study of Indonesian Positive Law and Islamic Law - Hasbiyalla, Iklil (STAI Miftahul Ula Nganjuk, 2024)
Marriage is a sacred institution in Islam and state law that aims to form a harmonious family. However, in practice, there are still many people who conduct marriages without official registration at the Office of Religious Affairs (KUA), known as nikah siri. This study aims to analyse the views of Islamic law and Indonesian state law on nikah siri, as well as the impacts of this practice. Under Islamic law, siri marriages can be considered valid if they fulfil the conditions and pillars of marriage, although the practice remains controversial. From the perspective of state law, siri marriages are not recognised because they do not fulfil the element of registration as stipulated in Marriage Law No 1 of 1974. While siri marriage has positive impacts, such as avoiding adultery, it also has greater negative impacts, especially in terms of legal protection for women and children. Therefore, marriage registration is a crucial aspect in safeguarding the rights of married couples as well as order in society.